REMEDIATION OF PHYSICS LEARNING TO REDUCE MISCONCEPTIONS OF GAS KINETIC THEORY MATERIAL BY USING THINK PAIR SHARE LEARNING SADDLES AT ROAD TRANSPORTATION SAFETY POLYTECHNIC CADETS - Langgeng Asmoro (Jurnal Scientia, 2023)
This study aims to determine whether the Think Pair Share method can reduce misconceptions in the Gas Kinetic Theory material and to determine the misconception profile of cadets of the Automotive Engineering Technology Study Program, Tegal Road Transportation Safety Polytechnic. The subjects in this study were cadets of the Automotive Engineering Technology Study Program, Tegal Road Transportation Safety Polytechnic, batch 9 Class A. The selection of this subject used a random sampling technique by assuming cadets had the same conditions and levels of misconceptions, this is. This is from the results of odd semester exams where the average grade score was almost the same for all grade 9 classes in Physics. This type of research is a pre-experimental design with a One Group Pret-Test-Post-Test design. Data was collected through interviews and test techniques in the form of diagnostic tests conducted before and after remediation learning. The source of data is obtained from the results of the Taruna. Data analysis was carried out quantitatively, including reducing the percentage of misconceptions of cadets and their misconception profiles. The results showed that remediation using the Think Pair Share method can reduce cadet misconceptions. The decrease in the percentage of misconceptions of cadets varies for each sub-material; in the sub-material, the properties of ideal gas misconceptions decreased by 44%. Decreased misconceptions in the sub-meter of the Ideal Gas Laws by 41%. Misconceptions in the sub-material of Gas Kinetic Theory decreased by 30%. Decrease in misconceptions in the energy equipartition submitted by 38%.